2019
DOI: 10.1126/scitranslmed.aaw0064
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for diffuse midline glioma from high-throughput combination drug screening

Abstract: Diffuse midline gliomas (DMGs) are universally lethal malignancies occurring chiefly during childhood and involving midline structures of the central nervous system, including thalamus, pons, and spinal cord. These molecularly related cancers are characterized by high prevalence of the histone H3K27M mutation. In search of effective therapeutic options, we examined multiple DMG cultures in sequential quantitative high-throughput screens (HTS) of 2706 approved and investigational drugs. This effort generated 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
134
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 44 publications
5
134
0
3
Order By: Relevance
“…Insights stemming from the identification of the oncohistone H3K27M as the unifying driver of these tumors, however, have introduced the potential for therapies targeting the dysregulated epigenetic milieu imparted by these recurrent mutations. Recognition of the aberrancies introduced across the epigenetic regulatory landscape by the H3K27M mutation has led several groups to explore and define epigenetic therapies such as histone demethylase inhibition (50) or histone deacetylase inhibition (20,47,51,52) as promising therapeutic strategies for DMG. Several of these agents are now moving forward in phase I clinical trials (NCT02717455, NCT03632317, NCT03566199) but have yet to demonstrate clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Insights stemming from the identification of the oncohistone H3K27M as the unifying driver of these tumors, however, have introduced the potential for therapies targeting the dysregulated epigenetic milieu imparted by these recurrent mutations. Recognition of the aberrancies introduced across the epigenetic regulatory landscape by the H3K27M mutation has led several groups to explore and define epigenetic therapies such as histone demethylase inhibition (50) or histone deacetylase inhibition (20,47,51,52) as promising therapeutic strategies for DMG. Several of these agents are now moving forward in phase I clinical trials (NCT02717455, NCT03632317, NCT03566199) but have yet to demonstrate clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct origin and associated molecular biology of DMGs provides the basis for more targeted therapeutic approaches, such as Chimeric Antigen Receptor T-cell 73 or histone deacetylase inhibitor therapy. 16,[74][75][76] In adults, the majority of diffuse (WHO II ) and anaplastic (WHO III ) gliomas but less than 10% of GBs (WHO IV ) harbor a mutation in the isocitrate dehydrogenase (IDH) genes. 7 The incidence of IDH mutant glioma increases abruptly in the third decade of life, and decreases in the fourth and fifth decade.…”
Section: Neurodevelopmental Origins Of Gliomasmentioning
confidence: 99%
“…That work demonstrated a modest benefit of the combination therapy with a ~20% increase in overall survival time of xenograft mice models 42 . Interestingly, the same study also showed varied combination effects between panobinostat and different CDK inhibitors 42 , i.e., they were synergistic, antagonistic or essentially absent depending on the individual CDK inhibitor. CDK2/4 kinases are known to regulate the subcellular localization, stability and function of Smad proteins downstream of TβRI via direct phosphorylation 31 .…”
Section: Discussionmentioning
confidence: 94%
“…This underscores the limited understanding of the molecular mechanisms that link epigenetics to gene transcription and phenotypical response in DIPG. During the revision of our manuscript, a new study on high-throughput combination drug screening against DIPG showed synergy between panobinostat and the proteasome inhibitor marizomib on inhibiting patient derived DIPG cells 42 . That work demonstrated a modest benefit of the combination therapy with a ~20% increase in overall survival time of xenograft mice models 42 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation